Terapi Suportif terhadap Keluarga Klien Skizofrenia - Wahyuni Thalib H Hasan, Sry; Daulima, Novy H.C; Putri, Yossie Susanti Eka (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effectiveness of supportive therapy for families of schizophrenia clients. The research method uses a systematic review approach. The research results show that supportive therapy is effective for families in clients treating schizophrenia. In conclusion, providing supportive therapy helps families understand obstacles and problems in treatment by resolving them using adaptive coping by utilizing internal and external sources of support. Keywords: Family, Schizophrenia, and Supportive Therapy